Advanced glycation endproduct-specific receptors in rat and mouse osteoblast-like cells: regulation with stages of differentiation - McCarthy, Antonio Desmond (1999)
Advanced glycation endproducts have been implicated in the development of diabetic complications. In addition, these products could also mediate certain bone alterations such as diabetic osteopenia. Several receptors specific for advanced glycation endproduct-modified proteins have been characterized in different cell types, contributing to the recognition and degradation of senescent proteins. In the present report, we investigated the possible presence of advanced glycation endproduct-binding proteins on osteoblast-like cells. Both UMR106 and MC3T3E1 cell lines express specific advanced glycation endproduct-binding sites, with an affinity constant between 0.4 and 1.7. 10(6) M(-1), depending on the stage of osteoblastic differentiation; and with a receptor capacity of 1.5-2.0. 10(7) sites/cell. Osteoblast-like cells were also found to participate both in the uptake and degradation of advanced glycation endproduct-modified bovine serum albumin at 37 degrees C. Radiolabelled ligand blotting studies confirmed the presence of several membrane binding proteins, with apparent molecular masses of 50, 45-40, 30, 25 and 18 kDa; the major bands corresponded to 30 and 25 kDa proteins. This study provides evidence of the presence of advanced glycation endproduct-specific binding sites, and for their regulation with the stage of differentiation, in two osteoblast-like cells in culture.